2021
DOI: 10.1002/adfm.202107312
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Confinement to Study the Crystallization Pathway of Calcium Sulfate

Abstract: Characterizing the pathways by which crystals form remains a significant challenge, particularly when multiple pathways operate simultaneously.Here, an imaging-based strategy is introduced that exploits confinement effects to track the evolution of a population of crystals in 3D and to characterize crystallization pathways. Focusing on calcium sulfate formation in aqueous solution at room temperature, precipitation is carried out within nanoporous media, which ensures that the crystals are fixed in position an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
(115 reference statements)
1
13
0
Order By: Relevance
“… 29 Stabilisation of bassanite for over 3 weeks was also reported in nanoscale pores. 15 Furthermore, there is ongoing discussion regarding the homogeneity of mixing during flow within the LC chip. In the set up here, bassanite is initially dispersed in 100% ethanol before the 9:1 [12 mM CaSO 4 ]:[ethanol] solution is flowed through the LC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 Stabilisation of bassanite for over 3 weeks was also reported in nanoscale pores. 15 Furthermore, there is ongoing discussion regarding the homogeneity of mixing during flow within the LC chip. In the set up here, bassanite is initially dispersed in 100% ethanol before the 9:1 [12 mM CaSO 4 ]:[ethanol] solution is flowed through the LC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 11 reported an amorphous precursor phase during the precipitation of gypsum from aqueous solution, an observation that was subsequently confirmed by others. [12][13][14][15] They also observed that bassanite formed prior to gypsum in solutions of concentration 15-50 mM, although ethanol (which can promote the formation of bassanite over gypsum) was used to wash the samples. Van Driessche et al 16 also identified bassanite as an intermediate in gypsum formation, using vacuum/solvent filtration and cryogenic quenching to prepare samples from solution concentrations of 50-150 mM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of X-ray computed tomography (CT) for 3D visualization of microstructures in geological materials has a variety of applications in the geosciences (Cnudde & Boone 2013), for example, to measure porosity (Zhang et al, 2019) and pore-scale processes (Hasan Sharul et al, 2020;Anduix-Canto et al, 2021), to determine the distribution of and association among minerals (Reyes et al, 2017;Guntoro et al, 2021;Da Ferraz Costa et al, 2022), which are useful properties in ore geology, and to determine particle properties (Wang et al, 2017;Miller & Lin 2018), which are important in the mineral processing industry (Videla et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that mineralization proceeds via multi-stage pathways including amorphous precursor phases [25][26][27][28][29][30][31][32][33][34][35][36][37] and/or bassanite intermediates [25][26][27][28][29][30][31]33] that convert to gypsum via oriented attachment of nanocrystals. [28] Sub-3 nanometer particles have been identified by time-resolved small-angle X-ray scattering (SAXS) as primary species during crystallization, [32] and amorphous calcium sulfate, which can be stabilized by confinement, [38] has been shown to precede bassanite formation. [26,32] All calcium sulfate polymorphs can be prepared selectively by controlling the ratio of water/organic solvent mixtures.…”
mentioning
confidence: 99%